1998
DOI: 10.1074/jbc.273.1.506
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Intron Involvement in the Mitogen-induced Expression of Zfp-36

Abstract: Zfp-36, the gene encoding the putative zinc finger protein tristetraprolin (TTP), is rapidly induced in fibroblasts by a variety of growth factors. Recent gene knockout experiments have shown that TTP-deficient mice developed arthritis, cachexia, and autoimmunity, all apparently mediated by an excess of tumor necrosis factor ␣. We recently showed that full serum inducibility of Zfp-36 requires elements in the promoter; in addition, removal of the single intron strikingly inhibited seruminduced TTP expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 58 publications
1
38
1
Order By: Relevance
“…11G and H) in which the hTTP-GFP fusion protein expression was driven by the native hTTP promoter and intron. Both the promoter and the single intron of TTP play important roles in its expression (23,24). Similar predominantly cytosolic distribution was seen in HeLa cells transfected with the same constructs (data not shown).…”
Section: Figsupporting
confidence: 60%
See 2 more Smart Citations
“…11G and H) in which the hTTP-GFP fusion protein expression was driven by the native hTTP promoter and intron. Both the promoter and the single intron of TTP play important roles in its expression (23,24). Similar predominantly cytosolic distribution was seen in HeLa cells transfected with the same constructs (data not shown).…”
Section: Figsupporting
confidence: 60%
“…supplemented with 10% fetal bovine serum, 100 U of penicillin per ml, and 100 g of streptomycin per ml. Transient transfection of 2 ϫ 10 6 cells with CMV.mTNF-␣ or other constructs in calcium-phosphate precipitates was performed as described previously (23,24), except that the transfection mixture was allowed to stay on the cells for 16 to 20 h and the glycerol shock step was omitted. In some experiments, pXGH5 (Nichols Institute Diagnostics) was also cotransfected to monitor transfection efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The TTP zinc finger mutants of expression plasmid CMV.hTTP.tag were made by the PCR primer-overlapping mutagenesis technique (21). Correct sequences of all intended mutations were confirmed by dRhodamine Terminator Cycle sequencing (PerkinElmer Life Sciences).…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…TTP is a protein encoded by Zfp36 in mice whose absence results in a severe autoimmune and inflammatory syndrome Taylor et al, 1996). TTP deficiency is associated with tumor necrosis factor-alpha (TNFα) overexpression (Blackshear, 2002;Carballo et al, 1998;Lai et al, 1998), and TTP has been shown to promote deadenylation and destruction of TNFα mRNA (Carballo et al, 1998;Lai et al, 1999). TTP may regulate overlapping aspects of immune cell function, inflammation and autoimmunity by targeting, in addition to TNFα, other essential mRNAs (Carballo et al, 1998;Carballo et al, 2000;Lai et al, 2006;Ogilvie et al, 2005).…”
Section: Introductionmentioning
confidence: 99%